UNIVERSITY STUDENTS’ PERCEPTIONS AND ATTITUDES TOWARD CLIL-BASED INSTRUCTION IN IRAQI EFL CONTEXTS - Hasanin Alaa Razaq; Hayder S. Alhkafaji; Aqeel Mery Mohammed (Scholars Digest Publishing, 2025)
This research explores how university students respond to learning their academic subjects through English under the Content and Language Integrated Learning (CLIL) framework. Conducted at the Islamic University’s College of Law and the Mathematics Department of the University of Kufa, the study examines students’ motivation and attitude toward receiving subject content in a foreign language. After introducing CLIL and outlining its educational principles, the paper contrasts students instructed via CLIL with those taught through traditional methods, accounting for gender differences as well. A total of 60 students — from both first and second academic years — completed a questionnaire assessing their perceptions of English-medium instruction. The analysis reveals that most participants expressed positive attitudes toward learning through CLIL, highlighting increased motivation not only to learn English but also to engage more deeply with the subject content. Overall, the findings suggest that CLIL can foster higher motivation and positive attitudes toward bilingual instruction in university-level education.
Keywords: CLIL, motivation, English-medium instruction, student attitudes, higher education.